A LIBERAL APPROACH TO THE ISLAMIC SYSTEM OF DHIMMAH - Tok, Nafiz; Sambur, Bilal; Mentzel, Peter C. (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
The system of dhimmah has been used to deal with diversity and conflict within Islamic societies. Will Kymlicka, a comtemporary liberal thinker, states that since the system of dhimmah has failed to foster individual autonomy, it should be discarded in the contemporary world. However, some liberals disagree with Kymlicka’s position. Chandran Kukathas, another prominent contemporary liberal thinker, opines that not autonomy, but freedom of conscience is the fundamental value each and every individual must possess. In this paper, we present the Islamic system of dhimmah and then turn to critically discuss two different liberal approaches of dealing with the differences. Finally, in the conclusion, it is argued that instead of discarding this approach, the system of dhimmah can be developed along liberal lines that can take freedom of conscience as the basis.